Update on trials examining effects of night-time blood pressure lowering drug treatment on prevention of cardiovascular disease - Chau Le Bao Ho; Christopher M. Reid (Open Exploration Publishing Inc., 2022)
Current evidence on benefits of night-time blood pressure (BP) lowering drug treatment on cardiovascular disease (CVD) prevention attributable to the Ambulatory Blood Pressure Monitoring in the Prediction of Cardiovascular Events and Effects of Chronotherapy (MAPEC) trial and Bedtime hypertension treatment improves cardiovascular risk reduction (Hygia) trials has raised concern on their validity and methodology. In this commentary, the authors have updated the progress of the ongoing trials that were planned to examine the effect of night-time BP lowering drug treatment on CVD prevention. As compared to MAPEC and Hygia trials, three pragmatic trials the Blood Pressure Medication Timing (BPMedtime) trial (US), the Treatment In Morning versus Evening (TIME) trial (UK), Bedmed and Bedmed-frail (Canada) were planned without ambulatory BP monitoring. The BPMedtime trial was stopped after the pilot phase due to underestimated sample size and insufficient funds. TIME trial (UK) had a similar issue when changing the sample size from 10,269 to more than 20,000 participants. The TIME trial was completed and the initial results showing that protection against heart attack, stroke and vascular death is not affected by whether antihypertensive medications are taken in the morning or evening. The full study of the TIME trial is published in December 2022. Bedmed and Bedmed-frail trials are ongoing and will be completed in 2023. Time of taking BP lowering drug should be determined by patients at their convenience to improve the adherence. There was no difference in adverse effects of taking BP lowering drugs at night or morning. Evidence on the effect of night-time treatment on CVD events is inconsistent. The results from ongoing trials in Canada will contribute evidence to the use of BP lowering drug treatment for the prevention of CVD.